1968
DOI: 10.1002/app.1968.070120912
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking poly(ethylene oxide) in dilute solutions by gamma rays

Abstract: SynopsisA high molecular weight poly(ethy1ene oxide) is gelled by radiation from a @' Co source. At concentrations of 0.25 to I we%, doses of 4.5 to 7.5 X lo4 rad cause gelation. The storage modulus of the gel formed increases linearly with additional dose to a plateau value and then remains constant during further irradiation. The dose needed to reach the plateau, D, in rads, and the plateau modulus G, in dynes per square centimeter, are related to the concentration c, in weight per cent: D, = 1.05 X 10% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…16 Van Brederode has found that the maximum modulus of poly(ethy1ene oxide) gels formed by gamma irradiation varies with concentration to the 2.25 power. 18 As the lower critical concentration is approached, the maximum modulus drops off rapidly as shown by the dotted lines in Figure 2.…”
Section: (4)mentioning
confidence: 93%
“…16 Van Brederode has found that the maximum modulus of poly(ethy1ene oxide) gels formed by gamma irradiation varies with concentration to the 2.25 power. 18 As the lower critical concentration is approached, the maximum modulus drops off rapidly as shown by the dotted lines in Figure 2.…”
Section: (4)mentioning
confidence: 93%
“…Slightly stiffer gels were formed at higher dose. The increase of the storage modulus G ′ and crosslink density with the irradiation dose has been observed for different radiation crosslinked gels, like PEO [ 58 ] and PVP hydrogels [ 59 ]. All nanocomposite gels had higher storage moduli, yield points and flow points compared to pure PEO gels at a certain dose.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of oxygen, however, poly(ethy1ene oxide) will gel when irradiated at the dosage of 4.5-7.5 X lo4 rad. 24 The scission of polymer chains will be more pronounced in the amorphous regions than in the crystalline regions. This might be due to the so-called "cage effect.…”
Section: Discussionmentioning
confidence: 99%